PENGEMBANGAN MODUL PEMBELAJARAN SIMULASI VIRTUAL PhET PADA MATERI LISTRIK DINAMIS - Yuda, Agung Candra; Nasir, Muhammad; ', Fakhruddin Z (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is aims to generate a learning module using virtual PhET simulationson the material of dynamic electric to be valid and proper for students to use as a self-learning materials. This research type using Research and Development (R&D) method with a model of the development are Four-D Model. The module was developed through four phases accordingto the development model being used, such as Define, Design, Develop and Dessiminates phase. The research data was obtained from the results of validation by three experts as validators. Instrument validation using content validity to assessment module by Badan Standar Nasional Pendidikan (BSNP) which consists of four feasibility aspects’s modules with 56 indicators assessment module. Validation was done through two phaseswhich is validation in first phase and validation in second phase. The results of the validation first phase, modules got an average value of 3.54 so the quality ofmodules at the validation phase one was “Good”. The results of the validation second phase obtained an average value of 4.01 so that the quality of modules at the validation second phase was“Good”. Feasibility of contents’s module obtained an average value of 3.8in the category “Good”, the feasibility of presentation’s module obtained an average value of 3.9 tocategory“Good”, feasibility of language’s modules obtained an average value of 3.9 to“Good”categoriy and feasibility of graphical’s modules scored an average of 4.01 in the “Good” category. Based on the results of feasibility aspect’s module, the module has fulfilled the criteria of Self Instructional, Self Contained, Stand Alone, Adaptive and User Friendly. Based on the results of the validation, it can be concluded that learning module using virtual PhET simulations on the material dynamic electricwas valid and proper to use as a self-learning materials for students.